Implementation of the Code of Ethics and School Administration within the Frame of Christian Leadership - Emmy Febriyani Situmorang; Elfrida Aritonang (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Abstract. Recently, more and more education research has focused on public reaction to the code of ethics due to the decline in the quality of education, school administration, teachers and education personnel in Christian leadership in education units. Educators and the public share the view that the root cause of this low quality of education lies with administrators. This study aims to explain the importance of ethical codes and educational administration in the success of a Christian leadership. This study uses a literature study approach, by comparing several main sources related to the code of ethics and educational administration. From the results of literature study, it can be concluded that the Code of Ethics and School Administration in Christian Leadership are related to each other. A teacher is required to have a Code of Ethics in carrying out his teaching duties, and run School Administration to support the school's achievement targets. This is done by referring to Christian Leadership based on the Written Word (Bible) and the Living Word (the Lord Jesus Himself).